THE USE OF DIALECTIC ETHNOGRAPHISMS IN WORKS OF ART (BASED ON THE MATERIAL OF M/NYZANOV) (TAMADDUN NURI JURNALI, 2025)
Ethnographisms are a cultural phenomenon that reflects the unique nationality of each people. This article discusses dialect-specific ethnographisms used in the language of the works of the master of artistic works M. Nizanov.